2015
DOI: 10.1016/j.addma.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of residual stress formation during the electron beam melting process for Inconel 718

Abstract: A computational modeling approach to simulate residual stress formation during the Electron Beam Melting (EBM) process within the Additive Manufacturing (AM) technologies for Inconel 718 is presented in this paper. The EBM process has demonstrated a high potential to fabricate components with complex geometries, but the resulting components are influenced by the thermal cycles observed during the manufacturing process. When processing nickel based superalloys, very high temperatures (approx. 1000 • C) are obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 20 publications
(24 reference statements)
3
75
0
1
Order By: Relevance
“…One of the main strategies mentioned in the literature is preheating the baseplate and/or powder bed before depositing or melting the first layer of material. Vastola et al (2016) calculated that a 50°C increase in the powder bed temperature in EBM showed a decrease of 20% in residual stresses, and this suggestion was similarly proposed by Prabhakar et al (2015) [83,84]. This strategy greatly reduces the thermal gradients and subsequent thermal stresses that are incumbent during processing.…”
Section: Modeling and Simulation Of Metal-based Additive Manufacturinmentioning
confidence: 86%
“…One of the main strategies mentioned in the literature is preheating the baseplate and/or powder bed before depositing or melting the first layer of material. Vastola et al (2016) calculated that a 50°C increase in the powder bed temperature in EBM showed a decrease of 20% in residual stresses, and this suggestion was similarly proposed by Prabhakar et al (2015) [83,84]. This strategy greatly reduces the thermal gradients and subsequent thermal stresses that are incumbent during processing.…”
Section: Modeling and Simulation Of Metal-based Additive Manufacturinmentioning
confidence: 86%
“…It is because the presence of thin fluid film reduces the friction coefficient as in Figure 10c,d and assist rapid oxide film reformation. In addition, the rapid solidifications during EBM process may develop residual stress field [31]. Elastic residual strains increase thermodynamic potential and ultimately accelerates electrochemical reaction of the mechanically disturbed surfaces [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] At the part scale, finite element (FE) modelling has proved to be useful to assess the influence of process parameters, 12 compute temperature distributions, 13,14 or evaluate distortions and residual stresses. [15][16][17] Recent contributions have introduced microstructure simulations of grain growth 18,19 and crystal plasticity, 20 melt-pool-scale models 3,21 and even multiscale and multiphysics solvers. [22][23][24][25][26] Furthermore, advanced frameworks (eg, grounded on multilevel hp-FE methods combined with implicit boundary methods 27 ) or applications to topology optimisation 28 have also been considered.…”
Section: Introductionmentioning
confidence: 99%